Geotechnical parametrization for shallow landslide modelling in Fradinhos, Vitória, Espírito Santo - Brazil - Effgen, Julia Frederica; Rocha, Pablo de Azevedo; Pires, Patrício José Moreira; Marchioro, Eberval (Sociedade & Natureza, 2020)
Vitória is prone to shallow landslides processes given its climatic and relief characteristics. The SHALSTAB model was used considering the soil’s cohesion to assess the susceptibility to shallow landsliding at the Fradinhos watershed, located in the Central Massif of Vitória. The parametrization was done with soil samples collected on three separate places in the watershed and submitted to shearing, permeability and texture tests. The soil samples were close to Oxisols (either developed from colluvium or not) and Inceptisols, with association with slope angle. Almost 95% of the watershed was modelled in a lower instability class (log Q/T > 2.2), with flow lines ranging from straight to divergent and variable slope angle. There is a strong association of the unstable areas to the drainage lines, hollows and steeper slopes. The modelling with results in critical rainfall, which considers the saturated transmissivity in its formulation, has the most unstable zones (with shallow landslide initiation potential with rainfalls of 2.5mm or less) related to drainage lines and steeper slopes. Closer to the Inceptisol soil sample, where we found the smallest values of saturated conductivity and soil thickness, the proneness to landslide initiation with lesser rainfalls is high. Close to the Oxisol developed from colluvium soil sample point, the critical rainfall for landslide initiation is elevated, with exception to areas with higher flow convergence and steeper slopes. The SHALSTAB model was an efficient tool to generate critical scenarios for shallow landslide susceptibility at the Fradinhos watershed, with greater proneness on hollows and steeper slopes.